Design, synthesis, antiviral activities of ferulic acid derivatives - Mao, Jin-long; Wang, Lei; Chen, Shu-jie; Yan, Bin; Xun, Li-ying; Li, Rui-cheng; Wang, Pei-chen; Zhao, Qi-tao (Frontiers in Pharmacology, 2023)
A series of novel ferulic acid derivatives were designed and synthesized, and the twenty-one compounds were evaluated for their antiviral activities against RSV, HSV-1 and EV71. These derivatives with the core structure of diphenyl acrylic acids had cis-trans isomers, which were confirmed by 1H NMR, HPLC, and UV-vis spectra for the first time. The A5 had a selective effect against RSV but no work on HSV-1 and EV71, which showed a therapeutic index (TI) of 32 and was significantly better than ferulic acid. The A5 had no scavenging effect on free radicals, but the A2 as the degradation of A5 showed an obvious scavenging effect on DPPH· and ABTS+·. In addition, the A5 had no toxicity to endothelial cells and even showed a proliferative effect. Therefore, the A5 is worth further optimizing its structure as a lead compound and investigating the mechanism of inhibiting RSV.